Parenthood among men diagnosed with cancer in childhood and early adulthood: trends over time in a Danish national cohort. Issue 9 (24th June 2021) - Sylvest, R; Vassard, D; Schmidt, L; Schmiegelow, K; Macklon, K T; Forman, J L; Pinborg, A
Abstract: STUDY QUESTION: Is the rate of fatherhood among men diagnosed with cancer in childhood and early adulthood different from men without cancer, and, if so, have the differences changed over time? SUMMARY ANSWER: Men diagnosed with cancer have had significantly reduced rates of fatherhood compared with undiagnosed men; however, the rates of fatherhood among the cancer survivors have increased markedly over time. WHAT IS KNOWN ALREADY: The number of children and young adolescents who survive cancer has steadily increased over recent decades, with a current 5-year survival rate of approximately 80%. Consequently, life circumstances after cancer have gained increasing importance, including the desire among survivors to have children and a family. ARTs to aid reproduction among cancer survivors have been developed, and fertility preservation is increasingly a topic being discussed before undergoing cancer treatment. But the potential for fertility preservation differs dependent on age at diagnosis and type of cancer. Earlier studies have shown a decreased fertility rate among survivors of child and adolescent cancer compared to those diagnosed in early adulthood. STUDY DESIGN, SIZE, DURATION: This study is a national, register-based cohort study. Men diagnosed with cancer in childhood and early adulthood (<30 years of age) were registered in the Danish Cancer Register in 1978–2016 (n = 9353). According to the time of diagnosis, each cancer-diagnosed man was randomly matched with 150 undiagnosed men from the background population within the same birth year. The men were followed until having their first child, death, migration or the end of the study (31 December 2017) in medical registers and socio-demographic population registers. PARTICIPANTS/MATERIALS, SETTING, METHODS: Fatherhood among the boys and young men diagnosed with cancer were compared with the age-matched comparison group in all statistical analyses. Cancer diagnoses were categorised as central nervous system (CNS) cancers, haematological cancers or solid cancers. Analyses were stratified by age at diagnosis (0–9, 10–19, 20–29 years) and time of diagnosis (1978–1989, 1990–1999, 2000–2009, 2010–2016). Death was incorporated as a competing risk in all analyses. MAIN RESULTS AND THE ROLE OF CHANCE: The study population consisted of 9353 boys and young men diagnosed with cancer between 1978 and 2016 and 1 386 493 men in the age-matched comparison group. Those surviving CNS cancer as young men had the lowest hazard ratio (HR) of fatherhood compared with the age-matched comparison group (HR 0.67, 95% CI 0.57–0.79), followed by survivors of haematological cancers (HR 0.90, 95% CI 0.81–1.01), while the highest chance of fatherhood was among survivors of solid cancers (HR 1.16, 95% CI 1.12–1.20) with a slightly increased HR compared with undiagnosed males. The HR of becoming a father increased over time. From the first decade to the last decade 30 years later, the HR of becoming a father increased for solid tumours (HR 0.78, 95% CI 0.73–0.83 to HR 1.08, 95% CI 0.95–1.22), haematological cancers (HR 0.64, 95% CI 0.53–0.79 to HR 0.97, 95% CI 0.73–1.30) and CNS cancers (HR 0.44, 95% CI 0.34–0.57 to HR 0.98, 95% CI 0.49–1.95) compared to the age-matched comparison group. Also, when compared with the age-matched comparison group, men diagnosed with cancer when aged 20–29 years were more likely became fathers over the time of the study (HR 0.80, 95% CI 0.74–0.86 to HR 1.08, 95% CI 0.96–1.22). LIMITATIONS, REASONS FOR CAUTION: The study was based on register data, and information was not available about the men's fertility potential, whether they had a desire to have children and whether it was possible for them to find a partner. Information about fertility preservation, e.g. sperm freezing, could also have provided additional insights. Furthermore, information about diagnosis and ART treatment would have been beneficial. WIDER IMPLICATIONS OF THE FINDINGS: Information and education of male patients diagnosed with cancer about fertility preservation options and their chances to create their own family is crucial. Reassuringly, time trends showed more men with a previous cancer diagnosis becoming fathers in recent years than in earlier years, reflecting that survival and fertility preservation have improved over time. STUDY FUNDING/COMPETING INTEREST(S): R.S. received a PhD grant from the Rosa Ebba Hansen Foundation and from the Health Foundation (J.nr. 15-B-0095). The funding for the establishment of the DANAC II Cohort was obtained from the Rosa Ebba Hansen Foundation. The authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.